SOSIALISASI MANFAAT WIRAUSAHA BAGI IBU-IBU RUMAHTANGGA DI DESA SINDANGGALIH KARANGAPAWITAN KABUPATEN GARUT - andhika, Andhika Lungguh Perceka; Anry Sutrisno; Hasbi Taobah Ramdani (LP4M STIKes Karsa Husada Garut, 2021)
Entrepreneurship is an important part of the economy of a country or region. One of the roles of entrepreneurship is as a means of alleviating small communities from poverty. Various entrepreneurial development efforts have been carried out, one of which is by generating and increasing new people or entrepreneurs in the field of entrepreneurship. The implementation of service activities uses the Lecture and Discussion method. The participants of the activity who took part in the socialization of the benefits of entrepreneurship were attended by 40 parents, fathers, mothers and children. The results of community service activities are so that people are motivated and interested in being able to optimize the potential of existing resources, both potential natural resources and human resources potential to be used as business opportunities or small or medium scale businesses. The public's interest in entrepreneurship in the field of entrepreneurship will have an impact on developments in the village. Community service activities carried out in the form of socialization with the theme